Synergistic chemotherapy and photothermal therapy of lung cancer using MoS2 nanosheets co-loaded with silybin and doxorubicin - Wang, Zhenjun; Xie, Zongtao; Liu, Chuanxin; Zhang, Xiaojun (Alexandria engineering journal, 2024)
The active ingredient in traditional Chinese medicine, silybin (SBN), is known to inhibit the proliferation of cancer cells and synergistically enhance the anticancer effects of the chemotherapy drug doxorubicin (DOX). However, the combination of SBN and DOX faces challenges such as a lack of targeting, short half-lives, different administration routes, and pharmacokinetic processes, which prevent the drug combination from effectively targeting tumors and diminish their synergistic potential, thereby limiting their in vivo antitumor effects. In response, this study proposes the development of a novel nanocarrier system based on molybdenum disulfide (MoS₂) modified with polyethylene glycol (PEG) and sialic acid (SA) to co-deliver SBN and DOX. This system is designed to trigger the release of the drugs in response to dual stimuli of pH and near-infrared light, increasing the intracellular concentration of the drugs and enhancing their synergistic interaction. The MoS₂-LPN-SBN/DOX nanosystem circulates within the body and specifically accumulates at tumor sites due to the enhanced permeability and retention (EPR) effect and SA-mediated active targeting. Upon exposure to near-infrared light, the system provides combined chemo- and photothermal therapy, leading to significant tumor suppression. This research offers a new approach and strategy for the clinical treatment of lung cancer, suggesting a promising pathway for enhancing the efficacy of traditional therapies.